1986
DOI: 10.1002/1097-0142(19861115)58:10<2343::aid-cncr2820581031>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma in pregnancy

Abstract: Renal cell carcinoma is the most common renal neoplasm associated with pregnancy. The most common presenting symptoms are pain and a palpable mass. Although renal neoplasms in pregnancy are rare, the pregnancy demands special consideration in the methods of diagnostic evaluation. The relationship between renal cell carcinoma and pregnancy is unclear. Treatment is usually radical nephrectomy regardless of the stage of pregnancy. Two new cases are presented with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
0
40
0
4
Order By: Relevance
“…3 Walker and Knight reviewed the presentation of renal cell carcinoma during pregnancy and found that the commonest presenting symptoms of such tumour were a palpable mass (88%), pain (50%), haematuria (47%), and hypertension (18%). 4 A subsequent review has suggested that there has been a change in the presentation of renal cell carcinoma in pregnant women, with diagnosis now more frequently made incidentally during ultrasound examination performed for other reasons, 5 as happened in this case.…”
Section: Discussionmentioning
confidence: 84%
“…3 Walker and Knight reviewed the presentation of renal cell carcinoma during pregnancy and found that the commonest presenting symptoms of such tumour were a palpable mass (88%), pain (50%), haematuria (47%), and hypertension (18%). 4 A subsequent review has suggested that there has been a change in the presentation of renal cell carcinoma in pregnant women, with diagnosis now more frequently made incidentally during ultrasound examination performed for other reasons, 5 as happened in this case.…”
Section: Discussionmentioning
confidence: 84%
“…Though it is a rare entity in pregnancy, it is the commonest of all the renal tumor occurring in pregnancy; the incidence being in 1 in 1000 cases. 4 Literature search up to 2013 revealed that only 102 cases of renal malignancies have been reported so far, out of which 86 cases were renal adenocarcinoma. 5 Smoking, obesity and hypertension are high risk factors for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…It seems from the literature review that the maternal and fetal prognosis is good and the results are comparable with non pregnant women with RCC. 4 Therefore few factors are taken into consideration while deciding the timing of surgery. First of all, it is known that the mean cell doubling time for an RCC is longer than 72 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Walker and Knight [5] reviewed the presentation of renal cell carcinoma during pregnancy and found that the commonest presenting symptoms of such tumours were a palpable mass (88%) and pain (50%). Hematuria and hypertension accounted for 47% and 18% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%